THE ROLE OF INDONESIAN STUDENTS IN LEARNING AND ASSISTING OPENING CEREMONIAL USING THREE LANGUAGES AT SPORTS EVENTS IN THAILAND - Lutfiah, Yuni; Putra, Aidil Syah Putra Syah; Rohim, Abdul (JCES (Journal of Character Education Society), 2025)
Abstrak: Pengabdian ini bertujuan untuk meningkatkan pemahaman dan keterampilan mahasiswi Indonesia dalam mendampingi acara seremonial internasional dengan penggunaan tiga bahasa, serta mengidentifikasi tantangan dan strategi efektif dalam komunikasi lintas budaya. Pendampingan dilakukan melalui empat tahapan utama, yaitu koordinasi awal, perencanaan, pelaksanaan, dan evaluasi. Hasil kegiatan menunjukkan bahwa penguasaan bahasa Thailand, Inggris, dan Indonesia serta pemahaman budaya sangat berperan dalam kelancaran acara. Penggunaan ketiga bahasa tersebut memastikan komunikasi yang efektif di antara peserta dengan latar belakang berbeda. Strategi pembimbingan, seperti pelatihan intensif, simulasi, dan pemanfaatan teknologi, terbukti mendukung peningkatan keterampilan mahasiswa. Meskipun terdapat tantangan dalam penguasaan bahasa, perbedaan budaya, dan kesiapan menghadapi perubahan mendadak, pendekatan kolaboratif dan evaluasi berkala membantu mahasiswa tampil lebih percaya diri dan profesional dalam menjalankan peran mereka. Dengan demikian, pengabdian ini menegaskan pentingnya keterampilan komunikasi dan pemahaman budaya dalam mendukung keberhasilan acara seremonial internasional serta mengembangkan kompetensi mahasiswa dalam interaksi lintas budaya.Abstract:  This service aims to improve the understanding and skills of Indonesian female students in assisting international ceremonial events with the use of three languages, as well as identifying challenges and effective strategies in cross-cultural communication. Assistance is carried out through four main stages, namely initial coordination, planning, implementation, and evaluation. The results showed that mastery of Thai, English, and Indonesian as well as cultural understanding were instrumental in the smooth running of the event. The use of the three languages ensured effective communication among participants with different backgrounds. Mentoring strategies, such as intensive training, simulation, and technology utilisation, proved to support the improvement of students' skills. Despite challenges in language acquisition, cultural differences, and preparedness for sudden changes, the collaborative approach and regular evaluations helped students perform more confidently and professionally in their roles. Thus, this service confirms the importance of communication skills and cultural understanding in supporting the success of international ceremonial events and developing students' competence in cross-cultural interactions.